Analisis Konsentrasi Logam Berat pada Sedimen dan Air Laut di Perairan Selat Rupat: Analysis of Heavy Metal Concentrations in Sediments and Sea Water in Rupat Strait Waters - Alan Krisbiantoro; Sri Fitrya Retnawaty; Yulia Fitri; Kurniati Utami (Life Science, 2025)
The Rupat Strait, located between Dumai City and Rupat Island in Riau Province, Indonesia, is an area with high industrial activity, including oil processing and maritime transportation. These activities contribute to the release of various pollutants, particularly heavy metals, into the marine environment. This study aimed to analyze the concentration of heavy metals (Pb, Cd, Cu, Fe, and Zn) in seawater and sediment samples to assess the extent of contamination and potential ecological risks. A total of nine observation stations and one control station were selected using purposive sampling. Field measurements of physical and chemical parameters were conducted in situ, while laboratory analyses of metal concentrations were performed using Atomic Absorption Spectrophotometry (AAS). The results showed that heavy metals were present at varying levels across all stations. The highest concentration was found for iron (Fe) in sediment at Station 9, reaching 18,476 ppm, while the lowest was cadmium (Cd) in seawater, with an average concentration of 0.001 ppm. Overall, metal concentrations in sediment were significantly higher than in seawater. These findings indicate a potential threat to benthic organisms and call for regular environmental monitoring. The study contributes valuable baseline data for marine pollution management and policy development in the Rupat Strait region.